Pelatihan Gamelan Degung Sebagai Upaya Penguatan Implementasi Kurikulum Merdeka Bagi Kelompok Kerja Guru Kec. Cisaat Kab. Sukabumi - Nurmeta, Irna; Faiz, Aiman; Az-Zahra, Fathia Frazna; Suganda , Siti Anisa; Ananda, Rizkia Wahyu; Anadella, Shakira; Maulidia, Reiza (LPPI UMN AL WASHLIYAH, 2024)
The usefulness of gamelan musical instruments that can be used as learning materials for P5 local wisdom themes has not been fully implemented in schools, especially for those who already have gamelan musical instruments. When viewed from the procurement of these musical instruments, the government has spent several funds to support traditional arts learning activities in schools, it's just that this has become a state loss because the implementation in the field has not been matched by the carrying capacity of qualified teaching staff, in the end, it cannot produce an activity or work for students. The utilization and use of gamelan equipment in this government program has not been running optimally, especially in the Cisaat sub-district, Sukabumi district. The method of implementing the service to KKG partners in the Cisaat sub-district, Sukabumi district consists of: Socialisation, Training, and Application of Technology. In this service activity, which focused on Gamelan training, the author and team used the Gamelan EduWeb website as a medium for teachers to learn the training material. The implementation results showed an increase in teachers' knowledge and skills in playing Gamelan after conducting training for 12x meetings. The implications of the training make teachers competent in teaching gamelan degung to students as an effort to implement character education in the Merdeka Curriculum.